Case Report: Cytomegalovirus-specific T-lymphocyte infusion for resistant cytomegalovirus retinitis - Saban, Tal; Shargian, Liat; Eiger-Moscovitch, Maya; Prockop, Susan; Doubrovina, Ekatarina; Yeshurun, Moshe; Kramer, Michal (Frontiers in Ophthalmology, 2023)
Purpose: We hereby describe a case of persistent cytomegalovirus (CMV) viremia and retinitis following allogeneic hematopoietic cell transplantation (HCT) that was successfully treated with infusion of CMV-specific cytotoxic T lymphocytes (CTL) despite previous treatment with Epstein Bar Virus (EBV) -specific CTL Observations: Following several anti- viral medication treatment trials that failed to eradicate the infectious process, the patient was treated with infusions of CMV-CTL from a biobank of cryopreserved virus-specific cells. Shortly after the first infusion, a remarkable response was noted. A few days after the second infusion, the retinitis resolved completely. No recurrence was noted at the one-year follow-up, and there was no evidence of GVHD. Conclusions and Importance: The case is unique for two reasons: use of virus-specific CTL for an indication of CMV retinitis; and successive administration, in the same patient, of third-party virus-specific CTL to treat two different infections (Epstein-Barr virus and cytomegalovirus) on two separate occasions following hematopoietic cell transplantation